2019
DOI: 10.1007/s00068-019-01227-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fracture redisplacement after reduction and cast immobilization of displaced distal radius fractures in children: a meta-analysis

Abstract: Purpose Displaced distal radius fractures in children are common and often reduced if necessary and immobilized in cast. Still, fracture redisplacement frequently occurs. This can be prevented by fixation of fracture fragments with K-wires, but until now, there are no clear guidelines for treatment with primary K-wire fixation. This meta-analysis aimed to identify risk factors for redisplacement after reduction and cast immobilization of displaced distal radius fractures in children, and thereby determine whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 41 publications
0
40
1
1
Order By: Relevance
“…The loss of radial height and inclination, however, was minimal, and fairly consistent, for both cast types. This is despite a mean cast index of 0.83 and 0.86 for the two groups, which are above the CI previous studies have deemed acceptable for distal forearm fractures (although it is acknowledged that this may not increase the likelihood of redisplacement) [11,12]. These results suggest that the soft-combi cast may be better at maintaining fracture position, although the differences seen were not statistically signi cant within our study sample.…”
Section: Discussioncontrasting
confidence: 78%
“…The loss of radial height and inclination, however, was minimal, and fairly consistent, for both cast types. This is despite a mean cast index of 0.83 and 0.86 for the two groups, which are above the CI previous studies have deemed acceptable for distal forearm fractures (although it is acknowledged that this may not increase the likelihood of redisplacement) [11,12]. These results suggest that the soft-combi cast may be better at maintaining fracture position, although the differences seen were not statistically signi cant within our study sample.…”
Section: Discussioncontrasting
confidence: 78%
“…Multivariate logistic analysis showed that age, AO classification, operation method, ipsilateral other fractures, comminted fractures, and postoperative exercise time were independent factors influencing the prognosis of distal radius fractures. e reason is that the older the patient, the more serious the calcium loss in the body, the osteoporosis, and the worse the body function and recovery function, and other complications often occur after treatment, which greatly increases the complexity, thus leading to a poor prognosis [22][23][24]. Patients with different AO classifications have different surgical difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of radial height and inclination, however, was minimal, and fairly consistent, for both cast types. This is despite a mean cast index of 0.83 and 0.86 for the two groups, which are above the CI previous studies have deemed acceptable for distal forearm fractures (although it is acknowledged that this may not increase the likelihood of redisplacement) [ 11 , 12 ]. These results suggest that the soft-combi cast may be better at maintaining fracture position, although the differences seen were not statistically significant within our study sample.…”
Section: Discussionmentioning
confidence: 59%
“…Manipulation was seen to improve, on average, all radiological parameters, with the greatest improvement being seen in the angulation. Anatomical reduction is a key factor to preventing DRF redisplacement after reduction and cast immobilisation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%